Sources of phosphorus for wintering beef heifer calves in dry lot. - Richardson, D.; Smith, E.F.; Menzies, C.S.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
In a previous test, it was found that phosphoric acid could be used as a source of phosphorus for beef heifers on dry bluestem pasture. A phosphorus balance study with lambs also indicated efficient utilization of phosphorus from phosphoric acid. This test was conducted to further evaluate phosphoric acid as a source of phosphorus in the wintering ration of beef calves in dry lot.
Keywords: Beef; Phosphorus; Gain; Feed efficiency